2010
DOI: 10.1071/en09156
|View full text |Cite
|
Sign up to set email alerts
|

Isoprene emission from phytoplankton monocultures: the relationship with chlorophyll-a, cell volume and carbon content

Abstract: Environmental context. Isoprene, a natural product of both terrestrial vegetation and marine organisms, is rapidly oxidised in the atmosphere, and thereby plays a key role in the regional budget of oxidants. Although isoprene production from terrestrial plants has been extensively investigated, production processes and emission rates from marine species are still poorly understood. We present results from laboratory experiments showing that isoprene is emitted from living phytoplankton cells at variable rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
110
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(118 citation statements)
references
References 49 publications
7
110
1
Order By: Relevance
“…During SPACES, with lower ocean temperatures and lower light levels than OASIS, the production rate is higher. This relationship would confirm the findings of two independent laboratory studies of Bonsang et al (2010) and Shaw et al (2003). Bonsang et al (2010) tested two species of cyanobacteria at 20 • C and found higher isoprene production rates than a different species tested by Shaw et al (2003) at 23 • C and even stronger light intensities.…”
Section: Drivers Of Isoprene Productionsupporting
confidence: 86%
See 2 more Smart Citations
“…During SPACES, with lower ocean temperatures and lower light levels than OASIS, the production rate is higher. This relationship would confirm the findings of two independent laboratory studies of Bonsang et al (2010) and Shaw et al (2003). Bonsang et al (2010) tested two species of cyanobacteria at 20 • C and found higher isoprene production rates than a different species tested by Shaw et al (2003) at 23 • C and even stronger light intensities.…”
Section: Drivers Of Isoprene Productionsupporting
confidence: 86%
“…This relationship would confirm the findings of two independent laboratory studies of Bonsang et al (2010) and Shaw et al (2003). Bonsang et al (2010) tested two species of cyanobacteria at 20 • C and found higher isoprene production rates than a different species tested by Shaw et al (2003) at 23 • C and even stronger light intensities. However, Exton et al (2013) measured the same rate as Shaw et al (2003) at 26 • C for one species, but a 5-times-higher production rate for another species at the same temperature.…”
Section: Drivers Of Isoprene Productionsupporting
confidence: 86%
See 1 more Smart Citation
“…Shaw et al (2003) also measured the production of a range of light non-methane hydrocarbons (C 2 to C 6 ); however, only isoprene was consistently produced by the five phytoplankton species studied. Bonsang et al (2010) grew a range of phytoplankton species, representing different major phylogenetic groups (cyanobacteria, diatoms, coccolithophores and chlorophytes), in laboratory cultures. All the phytoplankton investigated emitted isoprene, with the highest production rates (per unit chlorophyll a) occurring in the cyanobacteria (Trichodesmium and Synechococcus) and the lowest in the chlorophyte Dunaliella tertiolecta.…”
Section: Dimethylsulfoniopropionate (Dmsp) and Dimethysulfide (Dms)mentioning
confidence: 99%
“…Different PFTs have distinct impacts on the marine food web and biogeochemical cycling, e.g. variable relationships of different PFTs to isoprene production have been observed in laboratory experiments (Bonsang et al 2010). Ocean colour satellite observation is restricted to the near-surface layer, which varies from meters to about 60 m thick depending on the presence of optically-significant water constituents and the wavelength considered (Smith and Baker 1978).…”
Section: Marine Carbon Observations Frommentioning
confidence: 99%